Modelling of diffusional phenomena in structural alloys for high temperature applications - Gong, Y (2017)
This thesis is concerned with the physical metallurgy/corrosion of high temperature structural alloys, of the type used for some of the most demanding engineering applications yet devised by mankind. Both iron-based steels and nickel-based superalloys are used for such applications; the common thread in this thesis from the science perspective is the role played by defects such as vacancies which lead to degradation due to diffusional phenomena such as oxidation and creep. Modelling for typical diffusional behaviour is carried out at various length scales in this work. First, the vacancy formation free energy in fcc-nickel is calculated by using highly-accurate ab initio thermodynamics including relevant temperature effects such as phonon vibrations and magnetisms. Predictions show good agreement with experiments, with non-Arrhenius behaviour due to the anharmonicity suggested by calculations. Second, the oxidation kinetics is predicted for the Ni-Cr-O system by coupling CALPHAD thermodynamics and diffusional kinetics. A general (oxidation) diffusion model coupled with the homogenisation model is applied, allowing the treatment of metal, oxide and metal/oxide interface to be unified. Predicted oxidation kinetics considering oxide phases (halite, corundum and spinel) and metallic phases (fcc and bcc) show reasonable agreement with experiments. Proposed quantification of entropy-production potentially allows the long-debated question concerning the rate-controlling steps (phases) in high temperature corrosion process to be answered. Last, the failure (breakaway oxidation) mechanisms of a critical Fe9Cr1Mo nuclear component exposed to CO2 are studied by high-resolution characterisations. Based upon theories of carbon diffusion in ferrite and Boudouard surface reaction, the temperature-dependent lifetime — linked with carbon saturation in metal — is rationalised at accelerated conditions and is extrapolated to service conditions.